Barriers in Pedagogical Communication - Radojević, Tatjana S.; Kompirović, Tatjana P. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The field of research in this paper is aimed at examining the opinions of teachers and students in primary schools on the barriers in pedagogical communication in the classroom. The sample included one hundred and twenty-eight teachers and two hundred and ninety-seven students from VII to IX grade from seven primary schools from the southern and northern parts of Montenegro. The analysis of the results shows that there are more or less barriers, although there are also significant differences in the opinions of teachers and students regarding different barriers in pedagogical communication. Most teachers believe that barriers in pedagogical communication do not arise because of the source (teacher), but that the problem exists in other elements of the process.